Al-Rahnu system as an alternative to conventional pawnbroking for muslim community in Malaysia: an analysis study of legal framework and jurisdiction on the governance of al-Rahnu / Muhamad Zuhaili Saiman and Aiman Abdul Rashid Mohd Zainuddin - Saiman, Muhamad Zuhaili; Mohd Zainuddin, Aiman Abdul Rashid (Universiti Teknologi MARA, 2022)
Since the introduction of al-Rahnu as an alternative to conventional pawnbroking for Muslims in Malaysia in 1992, there are many organizations providing this service, and al-Rahnu from year to year is growing and expanding. However, there are issues and challenges to al-Rahnu because there are still Muslims who continue to conventional pawnbroking compared to al-Rahnu. The main purpose of this study is to examine the issues and challenges throughout the establishment of al-Rahnu as an alternative in Malaysia which is growing as an alternative that needs to be fully utilized by the Muslim community in Malaysia. This study will also analyse the factors that influence the factors of acceptance of al-Rahnu by the Muslim community. In addition, the study will try to identify the challenges faced by al-Rahnu. Therefore, the design of this study method is a qualitative method with a literature review approach and content and document analysis. The main findings of this study are the Muslim community's acceptance of shariah-compliant al-Rahnu proceeds as well as alternative money providers, capital for business and personal use. In addition, the challenge faced by al-Rahnu is the Muslim community's understanding of the sensitivity of a shariah-compliant instrument, knowledge of Islamic finance, as well as the ease of finding al-Rahnu places that are closer to the Muslim community.